2016
DOI: 10.1111/cen.13059
|View full text |Cite
|
Sign up to set email alerts
|

Decreased physical activity, reduced QoL and presence of debilitating fatigue in patients with Addison's disease

Abstract: Physical activity is decreased in patients with Addison's disease, combined with a reduced subjective health-related QoL and increased fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Numerous studies suggest that, in patients with AD, clinically relevant fatigue persists despite replacement therapy. For instance, Løvaŝ, Logeŧ, and Husebye (236) found that patients with AD selfreported reduced general health perception and vitality despite receiving replacement therapy with cortisone acetate and fludrocortisone. Similarly, van der Valk and colleagues (237) found that 48% of their patient sample (N = 328) self-reported abnormal fatigue; 61% reported severe fatigue.…”
Section: Sleep Disruptions In Admentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies suggest that, in patients with AD, clinically relevant fatigue persists despite replacement therapy. For instance, Løvaŝ, Logeŧ, and Husebye (236) found that patients with AD selfreported reduced general health perception and vitality despite receiving replacement therapy with cortisone acetate and fludrocortisone. Similarly, van der Valk and colleagues (237) found that 48% of their patient sample (N = 328) self-reported abnormal fatigue; 61% reported severe fatigue.…”
Section: Sleep Disruptions In Admentioning
confidence: 99%
“…Similarly, van der Valk and colleagues (237) found that 48% of their patient sample (N = 328) self-reported abnormal fatigue; 61% reported severe fatigue. Researchers postulate that reports of increased daytime fatigue may be due to reduced quality of sleep in patients with AD and that relatively increased doses of HC may contribute to these sleep disruptions (3,236,238).…”
Section: Sleep Disruptions In Admentioning
confidence: 99%
“…Current regimens of cortisol replacement therapy for patients lacking adrenal function do not replace ultradian rhythmicity and result in considerable morbidity. Several centers have confirmed that these treatment regimens result in impaired health-related quality of life (42)(43)(44)(45)(46)(47), adverse metabolic and cardiovascular risk profiles (48), increased levels of proinflammatory cytokines (49), and reduced activity, low motivation, and mental fatigue, with associated high levels of unemployment and disability benefits (43,(50)(51)(52). It was initially assumed that this was a direct consequence of the inability of oral medication to provide the normal circadian variation of cortisol, and that this could be improved by continuous s.c. infusions of the hormone.…”
mentioning
confidence: 99%
“…Due to the gradual onset and nonspecificity of initial symptoms, AI is a typical condition with a delayed diagnosis and a high rate of initial misdiagnosis (2,3). Although hormone replacement therapy results in improvement of symptoms in most patients, chronically treated patients report persistent morbidity and impairments in health-related quality of life (HR-QoL) (4)(5)(6)(7)(8). It is plausible that the impairments in HR-QoL are, at least partly, caused by intrinsic imperfections in hydrocortisone replacement strategies (5,9).…”
Section: Introductionmentioning
confidence: 99%